2013
DOI: 10.2807/1560-7917.es2013.18.46.20634
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the transmission of Salmonella from reptiles to children in Germany, July 2010 to October 2011

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 44 publications
1
55
0
3
Order By: Relevance
“…A large number of different Salmonella subspecies and serovars can be found on cloacal swabs of healthy captive chameleons (Woodward et al 1997;Geue and Löscher 2002;Willis et al 2002;Ebani et al 2005;Pees et al 2013). Our current study of 15 healthy captive female chameleons did not find any of the serovars previously reported, but extended the list found in this species with additional four different S. enterica serovars.…”
Section: Discussionmentioning
confidence: 35%
See 1 more Smart Citation
“…A large number of different Salmonella subspecies and serovars can be found on cloacal swabs of healthy captive chameleons (Woodward et al 1997;Geue and Löscher 2002;Willis et al 2002;Ebani et al 2005;Pees et al 2013). Our current study of 15 healthy captive female chameleons did not find any of the serovars previously reported, but extended the list found in this species with additional four different S. enterica serovars.…”
Section: Discussionmentioning
confidence: 35%
“…However, in stressed and/or immunosuppressed reptiles, Salmonella caused bacterial granuloma, septicaemia, pneumonia, nephritis, and death (Onderka and Finlayson 1985). Previous studies have identified Salmonella serovars Agona, Ajiobo, Arizonae, Durban, Ebrie, Enteritidis, Gaminara, Houten, Othmarschen, Pomona, Simi, Tel-el-kebir, IV 43:z 4 ,z 23 :-and IIIb 61:z 52 :z 53 in a few healthy captive individual chameleons (Woodward et al 1997;Geue and Löscher 2002;Willis et al 2002;Ebani et al 2005;Pees et al 2013). To date it is not known whether Salmonella species would be different or more widespread within a collection of healthy captive chameleons.…”
mentioning
confidence: 99%
“…Reptiles are often asymptomatic carriers of some important pathogenic bacteria [3][4][5]. In particular, several studies showed that cold-blooded animals are direct or indirect source of salmonellae in human infection outbreaks [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Pogona vitticeps unspecified reptile (Wikstrom et al 2014) Pogona vitticeps (Pees et al 2013 (Briones et al 2004). This could be due to the high number of reptile species bred in captivity together with the large variety of serotypes isolated from them.…”
Section: Eublepharis Maculariusmentioning
confidence: 99%
“…Infection can be contracted by direct contact with reptiles or indirectly from an environment contaminated by the faeces of infected animals. Cases of reptile-associated salmonellosis (RAS) have been observed in humans (e.g., Bertrand et al 2008;Pees et al 2013). RAS cases have been reported to be associated with young age and a higher rate of hospitalisation (Murphy and Oshin 2015).…”
mentioning
confidence: 99%